Calcium Aluminate Cement Blends Containing Bioactive Glass and Strontium for Biomaterial Applications - A.M. Barbosa; K.W. dos Santos; I. S. Gonçalves; P.M.S.C.M. Leite; A.S. Martorano; G. Grisote; L.M.S. Castro-Raucci; P.T. de Oliveira; L. Raniero; I.R. Oliveira (Materials Research, 2021)
Abstract In this work blends based on calcium aluminate cement (CAC) containing bioactive glass (BG) (5, 7.5 and 10 wt%) and strontium oxide (1 wt%) were produced aiming improve their bioactivity and the capacity to stimulate the bone regeneration. In the first part, the blends containing only BG were characterized as theoretical density, microhardness, uniaxial cold crush strength after SBF and apparent porosity and pore size distribution before and after SBF treatment. In the second part, bioactivity and cell culture tests were also conducted in the blends containing BG and strontium oxide. The addition of 7.5 wt% of BG in homogeneous calcium aluminate cement (CH) improved its mechanical properties as microhardness and uniaxial cold crushing strength. The blends were more bioactive due to the presence of a highly soluble amorphous phase as confirmed by means of SEM/EDX mainly for 7.5 wt% BG without and with Sr from 1 day in SBF. FTIR analyses indicated the formation the apatite-like phase by means of increase of intensity of the PO43- peaks after SBF treatment. All blends allowed the development of the osteoblastic phenotype and the formation of mineralized matrix increased due to the inclusion of BG and Sr promoting the osteogenesis process.